FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN GAGAL GINJAL TERMINAL PADA PENDERITA DIABETES MELLITUS TIPE 2 DI RSUD.DR. SOEDARSO DAN RSU. YARSI PONTIANAK - Wahyuni, Sri; Saleh, Ismael; Budiastutik, Indah (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2016)
Background: Patients with Type 2 diabetes have a 30-40% potentially experiencing renal disease during their lifetime, and a recurrence rate of 80% to 10-20% for 10-50 years. The incidence of terminal renal failure in hospitals. Dr. Soedarso his Pontianak each year has increased by 2013 the proportion of terminal renal failure 50 people has increased in 2014 to 65 and 2015 peirode April - May as many as 91 people. Kidney Failure Hemodialysis terminal if it is not run regularly every week then it will lead to death.Objective: This study aims to identify factors - factors related to the incidence of terminal renal failure in patients with diabetes mellitus in hospitals. Dr. Soedarso & RSU. Yarsi Pontianak.Methods: This study used a control desainKasus. Samples are 54 respondents (27 cases and 27 controls) were taken using accidental sampling technique using Chi - square with a 95% confidence level.Results: The results showed there is a significant relationship between status Hipertesi (p Value: 0,024) and smoking (p Value: 0,017), dietary protein and fat (p Value: 0,000) and exercise habits (p Value: 0,028), Variable unrelated were age (p Value: 0.750), duration of diabetes (p Value: 0,311) cholesterol levels (p Value: 0.584) and the habit of taking medication (p Value: 0.102).Suggestion: For hospitals. Dr. Soedarso & RSU.Yasri Pontianak to improve communication, information 7 education (KIE) to patients with Diabetes Mellitus need for dietary advice and the composition of the diet food. Planning sports activities for patients with DM and monitoring before, during and after exercise.Keywords: Status of Hypertension, Smoking Habit, DM, Kidney Failure Terminal